2020
DOI: 10.18705/2311-4495-2020-7-3-21-29
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations and complications in patients with covid-19

Abstract: It becomes apparent that the neurological complications of COVID-19 are significantly common, but in some cases, establishing a causal relationship is difficult. For example, a stroke can occur for reasons unrelated to coronavirus infection, while Guillain–Barré syndrome and meningoencephalitis are likely to be a parainfection. Only long-term epidemiological studies in large groups of patients can clarify some of these issues. This will help to better understand the mechanisms of development of complications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…A recently published retrospective study from Wuhan showed that in a sample of 214 confirmed COVID-19 patients, 36% had neurological manifestations [11]. All the lesions of the nervous system caused by COVID-19 encountered in practice can be divided into 3 groups: 1) manifestations of the central nervous system [headache and dizziness, acute cerebrovascular accident (ACV), encephalopathy, encephalitis, acute myelitis]; 2) lesions of the peripheral nervous system [anosmia, Guillain-Barré syndrome (GBS)]; 3) damage to skeletal muscles [2].…”
Section: The Main Findings and Resultsmentioning
confidence: 99%
“…A recently published retrospective study from Wuhan showed that in a sample of 214 confirmed COVID-19 patients, 36% had neurological manifestations [11]. All the lesions of the nervous system caused by COVID-19 encountered in practice can be divided into 3 groups: 1) manifestations of the central nervous system [headache and dizziness, acute cerebrovascular accident (ACV), encephalopathy, encephalitis, acute myelitis]; 2) lesions of the peripheral nervous system [anosmia, Guillain-Barré syndrome (GBS)]; 3) damage to skeletal muscles [2].…”
Section: The Main Findings and Resultsmentioning
confidence: 99%
“…К клиническим вариантам и проявлениям COVID-19 относятся острая респираторная вирусная инфекция, пневмония без дыхательной недостаточности, пневмония с острой дыхательной недостаточностью, сепсис, септический (инфекционно-токсический) шок. Возможные осложнения: острая сердечная недостаточность, острая почечная недостаточность, септический шок, геморрагический синдром на фоне снижения тромбоцитов крови, полиорганная недостаточность (нарушение функций многих органов и систем) [2,4].…”
Section: ______________________ Abstract ____________________________...unclassified
“…All COVID - 19 induced lesions of the nervous system encountered in practice can be divided into three groups: (1) pathological disorders of the CNS (headache, vertigo, insomnia, acute cerebrovascular accident (ACVA), encephalopathy, acute meningoencephalitis, acute disseminated encephalomyelitis, acute transverse myelitis); (2) lesions of the peripheral nervous system (chemosensory dysfunction, acute Guillain–Barré polyneuropathy syndrome); and (3) skeletal muscle lesions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%